The Effect Of Administration Of Ferous Sulfas On Iron Deficiency Anemia And Iron Deficiency Anemia With Stunting Aged 6 – 72 Months In Pandeglang, Banten And Its Review From Islamic View - Denis Tri Lestari; Wan Nedra; Muhammad Arsyad (Junior Medical Journal, 2022)
Iron deficiency anemia (IDA) is the most significant factor indicating low public health. Iron deficiency can cause disturbances or obstacles to growth, so that is related to stunting. Giving iron preparations is one of the efforts to reduce the incidence of IDA. Therefore, this study was conducted to determine the impact of iron supplementation on ADB and ADB with stunting aged 6-72 months. Al-Qur'an it emphasizes the importance to pay attention inhealth, one of themis by trying to seek treatment. This type of research uses a quasi-experimental method with a One-Group Pretest-Postest research design and taking samples with total sampling. The sample of this study was 30 toddlers aged 6-72 months in Kadugadung, Pandeglang, Banten.Based on the results of the study, after supplementation there was an increase in height (p 0.05), Hb, MCV, MCH and Ferritin values (p 0.05). However, MCHC levels did not show an increase (p0.05). Based on bivariate analysis using the chi-square on the relationship between ADB and stunting (p 0.05). Giving iron supplementation to children with ADB has a significant impact on Hemoglobin, MCV, MCH, Ferritin levels and stunting. However, there is no significant relationship between IDA and the incidence of stunting in children aged 6 - 72 months in Pandeglang, Banten. According to Islam, paying attention to health is one of the important things in maintaining benefit, one of them by consuming nutritious food as a iron supplementation in children with ADB and stunting.